The role of information communication technology (ICT) towards universal health coverage: the first steps of a telemedicine project in Ethiopia - Fassil Shiferaw; Maria Zolfo (Taylor & Francis Group, 2012)
Background: Eighty-five per cent of the Ethiopian population lives in remote areas, without access to modern health services. The limited health care budget, chronic shortage of health care workers and lack of incentives to retain those in remote areas further jeopardize the national health care delivery system. Recently, the application of information communication technology (ICT) to health care delivery and the use of telemedicine have raised hopes.Objective: This paper analyzes the challenges, failures and successes encountered in setting-up and implementing a telemedicine program in Ethiopia and provides possible recommendations for developing telemedicine strategies in countries with limited resources.Design: Ten sites in Ethiopia were selected to participate in this pilot between 2004 and 2006 and twenty physicians, two per site, were trained in the use of a store and forward telemedicine system, using a dial-up internet connection. Teledermatology, teleradiology and telepathology were the chosen disciplines for the electronic referrals, across the selected ten sites.Results: Telemedicine implementation does not depend only on technological factors, rather on e-government readiness, enabling policies, multisectoral involvement and capacity building processes. There is no perfect ‘one size fits all’ technology and the use of combined interoperable applications, according to the local context, is highly recommended.Conclusions: Telemedicine is still in a premature phase of development in Ethiopia and other sub-Saharan African countries, and it remains difficult to talk objectively about measurable impact of its use, even though it has demonstrated practical applicability beyond reasonable doubts.